If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25a + -8b + 4c + -6a + 13b + -1c = 0 Reorder the terms: 25a + -6a + -8b + 13b + 4c + -1c = 0 Combine like terms: 25a + -6a = 19a 19a + -8b + 13b + 4c + -1c = 0 Combine like terms: -8b + 13b = 5b 19a + 5b + 4c + -1c = 0 Combine like terms: 4c + -1c = 3c 19a + 5b + 3c = 0 Solving 19a + 5b + 3c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5b' to each side of the equation. 19a + 5b + -5b + 3c = 0 + -5b Combine like terms: 5b + -5b = 0 19a + 0 + 3c = 0 + -5b 19a + 3c = 0 + -5b Remove the zero: 19a + 3c = -5b Add '-3c' to each side of the equation. 19a + 3c + -3c = -5b + -3c Combine like terms: 3c + -3c = 0 19a + 0 = -5b + -3c 19a = -5b + -3c Divide each side by '19'. a = -0.2631578947b + -0.1578947368c Simplifying a = -0.2631578947b + -0.1578947368c
| 2a+12+a+(3a-9)=117 | | 6-18=m-4+14 | | (-3x^2-2x-2)+(2x^2+4x+4)= | | 9p-4p=-7 | | 27=3/7+6 | | 9x-4=65 | | 6+c=18 | | 3w+15=-4(w-2) | | 3w+15=-(w-2) | | 5-(1-x)=20 | | 7x+5y=-16 | | x=3(y/9) | | (4x^2+3x-5)(2x^3-10x+11)= | | 6x-15=6x | | 2x+7=10x+9 | | a-4/9a=-7/9 | | 1/2x^3-1/2x^2-24=0 | | 7=-2n-5 | | p(x)-750x^2+15000x=0 | | 0.8(25m-20n)= | | 5(2n-1)=5 | | -6+2t=3t-(6+5) | | 3x=y/9 | | ((d-4)/4)^2=49 | | -102=-6(8n+1) | | 2(3-6n)=102 | | 3[m+(-5)]=2m+10 | | 30+-10= | | 5-4(8x-2)=0 | | -5x+5(8x-6)=180 | | A=7/4 | | a+2=6a-6 |